2016
DOI: 10.1155/2016/1015796
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Lower Urinary Tract Symptoms among Middle Aged and Elderly Nigerian Men: Impact on Quality of Life

Abstract: Objectives. To compare the severity of LUTS among middle aged and elderly Nigerian men and determine the influence of LUTS severity on QoL. Methods. This cross-sectional study was conducted among new patients presenting with LUTS attending Urology clinic between 2011 and 2015. Assessment of symptoms was based on IPSS and bother score completed by the eligible subjects on the same day of their clinic visits. Results. Four hundred patients were studied comprising 229 middle aged and 171 elderly men. Interquartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
2
3
2
Order By: Relevance
“…There was statistically significant relationship between the severity of LUTS assessed by IPSS and the QoL. This finding is consistent with the study by Patrick et al [12] who concluded that it might be better to use the quality of life (QoL) as determinant of the choice of treatment, rather than the IPSS scores alone for prompt treatment of LUTS. Patients presented more with moderate IPSS symptoms (55.2%), mild symptoms (11.4%) and severe symptoms (33.4%), with the findings similar to that of Ofoha et al [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There was statistically significant relationship between the severity of LUTS assessed by IPSS and the QoL. This finding is consistent with the study by Patrick et al [12] who concluded that it might be better to use the quality of life (QoL) as determinant of the choice of treatment, rather than the IPSS scores alone for prompt treatment of LUTS. Patients presented more with moderate IPSS symptoms (55.2%), mild symptoms (11.4%) and severe symptoms (33.4%), with the findings similar to that of Ofoha et al [17].…”
Section: Discussionsupporting
confidence: 90%
“…Benign prostatic hyperplasia and lower urinary tract symptoms are quite prevalent in men with advancing age [4]. Clinical BPH may not be life threatening; however, its manifestation as LUTS interferes with QoL [12]. In this study, the mean age of participants was 64.2 ± 9.0 years with a range of 40 to 95 years.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…There was also a strong positive correlation between the IPSS and QoL. This is similar to the findings of Adegun et al [21]. They further suggested that the QoL should serve as the basis of treatment rather than the IPSS.…”
Section: Discussionsupporting
confidence: 87%
“…The age of the patients did not correlate the overall severity of NMS; however, the older age groups were found to have worse symptoms in the attention/memory, gastrointestinal, and urinary domains which could be due to additional confounders such as senile dementia, obstructive uropathy, and constipation which are more common with increasing age 2224. The findings in this study were contrary to the results of another study in Estonia, where age was found to be associated with worsening NMS.…”
Section: Discussionmentioning
confidence: 86%